MINING MACHINES ELEMENTS PACKING AND SECURING ON PLATFORM CONTAINER - Maria CIEŚLA; Tadeusz OPASIAK (Scientific Journal of Silesian University of Technology. Series Transport)
The scientific purpose of this paper was to analyse the problem related to intermodal transportation of mining components packed in containers or other cargo transport units coupled with the problem of its proper securing. In this article, the issue of exposing the load to the effects of inertia forces which might cause unintentional movement is presented. The methods of securing the heavy load in cargo transport units are reviewed in the context of cargo immobilisation possibilities while reducing the load sensitivity to mechanical forces. The research part of this article presents the methods of packing and securing an atypical load, which is a part of a mining machine weighing 18t. This paper presents the results of calculations of inertia forces acting on the transported cargo, packed on a container platform. Based on the results, the cross fixing method was selected to secure the cargo and further decisions were made on the type and quantity of conveyor lashings necessary for the safe and correct carriage of the atypical load.